Comparative genomics of Cochlodinium and other marine dinoflagellates as inferred from Genome sequence analysis - Chin, Grace Joy Wei Lie (Universiti Malaysia Sabah, 2011)
Cochlodinium polykrikoides is one of the causative agents for harmful algal blooms occurring in the west cost of Sabah, which result in massive economic damage to the aquaculture and mariculture industries. Currently, limited information is available on the genomics of C polykrikoides. The objectives of this study were to develop a protocol for the construction of an expressed sequence tag (EST) library for C polykrikoides cells cultured under normalized conditions, to design gene specific primers using sequence information of related dinoflagellates and to test the gene specific primers against the DNA and RNA of C po/ykrikoides. Cochlodinium polykrikoides stock cultures were obtained from the Unit for Harmful Algal Blooms Studies (UHABs) of the Borneo Marine Research Institute, Universiti Malaysia Sa bah and cultured in f /2 medium. Optimization of total RNA isolation from C polykrikoides was performed using five different methods. Among the five methods tried, the RNA isolation protocol using the TRizol reagent produced the best results. Synthesis of cDNA was performed on successfully isolated RNA samples followed by cloning and direct sequencing of the purified clones. In addition, fourteen gene specific primer pairs were designed and synthesized using sequence information from other harmful algae species. Genomic DNA samples isolated from C polykn1<oides cells were used as templates for the PCR amplification carried out using the synthesized gene specific primers. Amplification products from three gene specific primers, psaAl F/R, COX-1 F/R and ATPsynC F/R were purified and subsequently cloned and directly sequenced. Based on the sequencing results, the cloned products were found to produce identity matches to genes encoding products from similar and related protein families, such as the oxidoreductases and cytochrome oxidases.